Introducing a Morbidity and Mortality Conference in Rwanda - Abahuje, Egide; Nzeyimana, Innocent; Rickard, Jennifer L. (Journal of surgical education, 2017)
To assess the structure, format, and educational features of a morbidity and mortality (M&M) conference in Rwanda. To determine factors associated with adverse events and to define opportunities for improvement. Retrospective, descriptive study of all cases presented at a surgical M&M conference over a 1-year period. Cases were reviewed for factors associated with adverse events and opportunities for improvement. Factors were characterized as delays in presentation, delays in diagnosis, delays in the operating room, errors in judgment, technical errors, advanced disease, and missing resources or malnutrition. Opportunities for improvement were categorized at the physician or hospital level. University Teaching Hospital of Kigali, a tertiary referral hospital in Rwanda. Cases presented at the surgical M&M conference over a 1-year period. Over a 1-year period, there were a total of 2231 operations with 131 in-hospital mortalities. There were 62 patients discussed at M&M conference. Of those discussed, there were 34 (55%) in-hospital deaths and 32 (52%) unplanned reoperations. Common diagnostic categories included 30 (48%) gastrointestinal, 15 (24%) trauma, and 10 (16%) neoplasm. Delays were commonly cited factors affecting outcomes. There were 22 (35%) delays in presentation, 23 (37%) delays in diagnosis or management, and 20 (32%) delays to the operating room. Errors in judgment occurred in 15 (24%) cases and technical errors occurred in 18 (29%) cases. Twenty-three (37%) patients had a critical resource missing and 17 (27%) patients had advanced disease. Malnutrition was associated with 11 (18%) adverse events. Participants identified opportunities for improvement in 48 (77%) cases. M&M conference can be used in a low-resource setting as an educational tool to address core competencies of practice-based learning and improvement and systems-based practice. It can define factors associated with surgical adverse events and opportunities for improvement at the physician and hospital levels.